Technical efficiency and yield gap of potato: Case from central hills of Nepal - Tiwari, Narayan Prasad; Sapkota, Umesh (Nepal Agriculture Research Journal, 2025)
This study evaluates the technical efficiency and yield gap in potato production in two hilly district of Nepal using Stochastic Frontier Analysis (SFA). Potato being major contributor of AGDP in Nepal faced lower productivity, one of the major reasons is inefficient use of inputs. With the objective of identifying determinants for inefficiency cross sectional survey of 184 potato growers was conducted, with data analyzed using stochastic frontier model. The study revealed average technical efficiency of 84.32%, with yield gap of 2441 kg/ha suggesting scope of increase potato production through improve resource allocation and management practices. The inputs like chemical fertilizer, FYM, and farm size have positive and significant relation with production whereas seed tuber use have negative and significant relation with production of potato. Contact with extension agents have negative coefficient suggest that increased in interaction with extension agents reduces inefficiency. Similarly major source of income(agriculture), suggesting that farmers who have agriculture as major source tends to have higher inefficiency in potato production. The negative coefficient for variety type (Rojita) shows significant relation with type of variety and inefficiency of farm production. The study suggest opportunity to increase the output by 15.68 % of potato production with resource optimizations and good management practices. Policy maker should focus on reach of extension activities to farmers field which reduces the farm efficiency and use of improved variety.